From Form to Function: Isomorphic Mimicry, Planned Development Endeavors, and Implementation Outcomes in Nepal’s Federal Periodic Planning - Baburam Bhul (Indonesian Association for Public Administration, 2026)
Despite nearly seven decades of periodic development planning experience, imple- mentation gaps remain pervasive and hinder the attainment of the planned devel- opment outcomes. While the literature has established that actual outcomes have differed significantly from the targets specified in development plans, the institution- al processes underpinning this chronic implementation problem have been studied less systematically. This study examines Nepal’s periodic planning regime, from the First Five-Year Plan (1956–1961) to the Fifteenth Periodic Plan (2019/20–2023/24), through the interpretive frame of isomorphic mimicry. Relying on a qualitative lon- gitudinal design, this study uses documentary analysis and process tracing to investi- gate changes in planning institutions, governance reform efforts, and implementation outcomes over time. This study operationalizes the concept of isomorphic mimicry through four observable indicators: the adoption of internationally propagated plan- ning models, an increase in the number of formal planning institutions, the presence of persistent plan-performance gaps, and repeated institutional reforms without cor- responding improvements in implementation capabilities. The findings show that as Nepal’s periodic plans became more integrated into global development objectives, literacy, poverty, human development, and income per capita improved. However, implementation capability trailed substantially behind the plan’s aspirations through- out. The study emphasizes the argument for planning-related isomorphism and demonstrates that improving institutional skills is an essential condition for trans- forming planning objectives into meaningful development outcomes.